Efektivitas Model Problem Based Learning Berbantuan LKPD Digital Terhadap Kemampuan Pemecahan Masalah Pada Materi SPLDV - Prayitno, Sudi; Kertiyani, Ni Made Intan; Ernawati, Ernawati (Griya Journal of Mathematics Education and Application, 2025)
This study was motivated by the low problem-solving skills of students, which were caused by the use of conventional learning models that were ineffective and the lack of innovative learning media. This study aims to determine the effectiveness of the problem-based learning model assisted by digital worksheets on the problem-solving skills of ninth-grade students at SMPN 19 Mataram in the 2025/2026 academic year. This study was a quasi-experimental design with a posttest-only control design. The sampling technique used in this study is purposive sampling. The sample in this study consisted of students in class IX A as the experimental class who received treatment using the PBL model assisted by digital worksheets and students in class IX D as the control class who used the conventional model. The calculation results showed that the average score of the experimental class (78.25) was higher than that of the control class (60.61). Then, the results of the independent sample t-test with a significance of 5% obtained a sig. value (2-tailed) = 0.001 < 0.05. Furthermore, the value . The effect size test results showed a value of 1.344, which, based on the criteria, has a high effect. Therefore, the application of the PBL model assisted by digital LKPD is able to increase students' active involvement in constructing knowledge to solve problems. Thus, it can be concluded that the use of the PBL model assisted by digital worksheets is effective in improving the problem-solving skills of ninth-grade students at SMPN 19 Mataram in the 2025/2026 academic year.